Reading Literature in Uzbekistan: From Local to Global Thinking (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In the pre-independence period of Uzbekistan, reading literature was also based on communist ideology. Today’s globalization is also impact on interpreting literary art. Because through the universal approach to a specific reality, readersr might discover new interpretations in the harmony of national and international concepts while analyzing the literary texts. At the same time global integration is negatively influencing on nation’s thought, especially, young people’s thinking and it causes a lot of cultural loses, treats to values in the sense «covering the entire globe", "exceeding", "exceeding the limit" .In this article, the main principles of reading literature, positive and negative impact of globalization on students thought, positive, at the same time negative consequences of global integration is analyzed in the local and global context. And influence of ideological inertia of Soviet Imperia to reading literature, life style of old and young generation will also be discussed in the case of Uzbekistan.